2013
DOI: 10.1016/j.plantsci.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Mineral stress affects the cell wall composition of grapevine (Vitis vinifera L.) callus

Abstract: Grapevine (Vitis vinifera L.) is one of the most economically important fruit crops in the world. Deficit in nitrogen, phosphorus and sulfur nutrition impairs essential metabolic pathways. The influence of mineral stress in the composition of the plant cell wall (CW) has received residual attention. Using grapevine callus as a model system, 6 weeks deficiency of those elements caused a significant decrease in growth. Callus CWs were analyzed by Fourier transform infrared spectroscopy (FT-IR), by quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 82 publications
6
43
0
Order By: Relevance
“…For example grapevine callus subjected to deficiency in S, N, and P showed walls with a decreased content in cellulose, increased lignin amount, alterations in the methylesterification of pectin (Fernandes et al, 2013). These results show how plant cell walls are remodeled in response to mineral deficits and how their composition is modified according to the stress condition applied.…”
Section: The Plant Cell Wall: a Living Structurementioning
confidence: 99%
“…For example grapevine callus subjected to deficiency in S, N, and P showed walls with a decreased content in cellulose, increased lignin amount, alterations in the methylesterification of pectin (Fernandes et al, 2013). These results show how plant cell walls are remodeled in response to mineral deficits and how their composition is modified according to the stress condition applied.…”
Section: The Plant Cell Wall: a Living Structurementioning
confidence: 99%
“…They also found that P deficiency increased Al tolerance and decreased Al accumulation in rice roots. Although the mechanism is unknown, deficiency of P affects the cell wall composition (Fernandes et al 2013). For example, in Arabidopsis, P deficiency caused decreased concentrations of pectin and hemicellulose of the cell wall (Zhu et al 2012), although it is unknown whether similar changes occur in wheat.…”
Section: P0mentioning
confidence: 99%
“…110 During water stress, microtubules are eliminated by proteolytic degradation (Wang et al, 2011) followed by cellulose microfibril re-organization and activation of phospholipase-D dependent signaling during osmotic adaptation. [111][112][113] Release of DAMPs and CWI modifications can be perceived by membrane receptors, communicated by trans-membrane channels and can trigger internal cell signaling cascades to activate appropriate response genes. Thus, the large family of receptor like kinases (RLKs), arabinogalactan proteins, the Mitogen-Activated Protein Kinase (MAPK) pathway and the Target of Rapamycin (TOR) pathway have been suggested Figure 1.…”
Section: Cell Wall Integrity Perceptionmentioning
confidence: 99%